Aberration of mind : suicide and suffering in the Civil War-era South - Sommerville, Diane Miller (The University of North Carolina Press, 2018)
This book studies the meaning of suicide in the nineteenth-century South and how that meaning changed, if at all, as a result of the Civil War and its aftermath. It looks at the whole South while providing a more thorough examination than previous books of the dynamics of both the racial and gendered dimensions of suicide in the South during the long Civil War Era.